Efficacy of vitamin C vaginal tablets in the treatment of bacterial vaginosis: a randomised, double blind, placebo controlled clinical trial - Petersen, Eiko E; Genet, Margherita; Caserini, Maurizio; Palmieri, Renata (Arzneimittelforschung, 2011)
A randomised, double blind, parallel groups, placebo controlled clinical trial was conducted to assess the efficacy and safety profile of 250 mg ascorbic acid (Vit. C, Vagi C®) in women with bacterial vaginosis (BV). Overall, 277 out-patients with at least three of the following signs (white discharge that smoothly coats the vaginal walls, pH of vaginal fluid >4.5, a fishy odour of vaginal discharge before or after addition of 10% KOH and presence of clue cells on microscopic examination) were randomised to apply a tablet deeply into the vagina once daily for 6 days. The primary efficacy endpoint was the cure rate, defined as the recovery of all inclusion criteria. In the intent-to-treat (ITT) population, cure was achieved by 55.3 % of patients with Vit. C (n = 141) and by 25.7 % of patients with placebo (n = 136). The between-group difference was 29.6 % (p < 0.001). In the per-protocol (PP) population, cure rate was 66.4 % with Vit. C (n = 116) and 27.1 % with placebo (n = 118), respectively. Between-group difference was 39.3 % (p < 0.001). In a subset of patients with centralised evaluation of the vaginal swab, cure in ITT was achieved by 86.3 % of patients with Vit. C (n = 51) and by 7.6 % of patients with placebo (n = 53), the between-group difference was 78.7 % (p < 0.0001). Cure rate in PP was 86.0 % with Vit. C (n = 50) and 6.1 % with placebo (n = 49), between-group difference was 79.9 % (p < 0.0001). Both Vit. C and placebo were well tolerated and no differences in safety profile were evident between groups.The results support an effective and safe use of silicon-coated Vit. C vaginal tablets in the management of BV.
Keywords: Ascorbic acid vaginal tablets; Bacterial vaginosis; Vaginal pH; Vitamin C vaginal tablets